Étude de la dispersion d'un gisement d'or dans les sédiments glaciaires : le cas d'Amaruq (Nunavut, Canada) - De Bronac de Vazelhes, Victor (Université Laval, 2019)
On the Amaruq property (Nunavut, CA), the gold mineralization is covered by a patchwork of glacial sediments, including trains of mineralized debris dispersed over large surfaces. This project aims to define the deposit mineralogical and multi-elemental signatures in surface sediments to guide exploration in the area. A total of 61 samples were collected from frost boils along four NNW transects, parallel to the major ice flow direction, in order to assess the spatial variability of the deposit signature using till matrix geochemistry and indicator minerals. Four profiles in frost boils were sampled, one in each transect, in order to document trace elements depth variation. The scheelite geochemical signature from the deposit is compared to that in till from the Whale Tail transect to test its applicability in drift prospecting. Three out of four frost boil profiles exposed constant trace elements concentrations at depth, reflecting a good till homogenization by cryoturbation. Therefore, frost boils are a suitable medium of sampling for exploration purpose in permafrost terrain. Principal component analysis (PCA) of a previous till survey by Agnico Eagle Mines ldt (AEM) and transect samples define the ultramafic/mafic host rock of the mineralization and a pathfinder element suite characteristic of lode gold deposits (PC1 and PC2, respectively). Kriging of PC1 and PC2 defines a dispersal train oriented NNW, down ice of known mineralization. In the eastern part of the property, covered mostly by a distal till forming drumlinoid ridges, indicator mineral counts (IM: gold and scheelite) increase to a maximum approximately 1.4 km down ice from the outcropping zone. Western transects, largely covered by a proximal till forming morainal ridges, show a sharp increase of counts directly down-ice of mineralization. The difference in glacial transport between these two sectors represents a local change of ice dynamic and shows the importance of understanding the local context in exploration when interpreting glacial ...